High‐fidelity finite element modeling of the seismic response of prefabricated steel stairs - Sorosh, Shokrullah; Hutchinson, Tara C.; Ryan, Keri L.; Smith, Kevin; Belvin, Robert; Black, Cameron (Earthquake engineering & structural dynamics, 2024)
Advancing the seismic resilience of building systems is an active area of research in earthquake engineering. Ensuring safe egress in and out of buildings during extreme events, such as an earthquake, is essential to supporting this effort. To this end, understanding the seismic response of stairs facilitates the robust design of egress systems to ensure they can remain operable after an earthquake. From prior earthquake events and physical experiments, it is understood that stairs with a flight to landing fixed connection at multiple levels within a building are prone to damage. In addition, the stair system with flight to landing fixed attachments may affect the dynamic behavior of the building. To accommodate seismic inter‐story drifts, a kinematically free connection between the stairs and landing has been proposed. Herein this connection is referred to as a drift‐compatible stair connection. To investigate and aid in the design of such a connection, a unique set of shake table experiments were conducted at the University of Nevada, Reno. In this paper, an overview of these tests is presented, and a high‐fidelity finite element model of the tested stair system is used to predict the responses measured during these experiments. Developed in Abaqus, the robustness of the modeled stair unit is investigated considering a variety of contrasting connections, namely, drift‐compatible connections, fixed ends and one end fixed and the other free. Results from these numerical simulations offer guidance towards development of simplified models of multi‐level stair subsystems. Such models are needed when investigating seismic resilience of building systems across a wider range of hazard levels. Furthermore, best practices observed utilizing the models developed and evaluated herein against experimental data will be useful for subsequent analysis of larger stair tower models, such as the 10‐story stair system implemented in the NHERI Tall Wood mass timber building with post‐tensioned rocking walls, conducted in 2023 at the UC San Diego Large High‐Performance Outdoor Shake Table.